Pharmacokinetics of twice-daily versus once-daily dosing with granular slow-release para-aminosalicylic acid in adults on second-line anti-tuberculosis and antiretroviral treatment - De Kock, Lizanne (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc in Medical Science)--Stellenbosch University, 2013.